Conciliating artisanal and recreational fisheries in Anegada Bay, Argentina - Llompart, Facundo Manuel (2017)
Recreational and artisanal fisheries are common activities in Latin America often interpreted as competitors due to the use of common-pool resources in coastal areas. Conflicts between the (historical) artisanal fisheries (AF) and recreational fisheries (RF) in Anegada Bay resulted in the prohibition of the former. This study addresses key fisheries characteristics to detect the degree of spatio-temporal overlap between them considering the annual dynamic of the coastal fish assemblage and proposed management alternatives. Both fisheries exerted different fishing effort coinciding with the dynamic of the fish assemblages but partial temporal and spatial overlap where apparent especially during one month. However, both fisheries focused their catches on different target species thus greatly reducing the overlap in resource use. Moreover, the low proportion of juveniles caught, limited fishing effort using selective bottom gillnets and scarce total harvest (168 tonnes/years) for AF compared with those of RF harvest (631 tonnes/years) in Anegada Bay poorly justifies the actual prohibition. However, the vulnerability index of AF landings resulted in higher values than the RF. To resolve conflicts, a co-management including AF, RF and industrial (trawl) stakeholders and non-fishing community is suggested. Because of the economic importance of fishing for local people, an efficient inter and intra-sector communications process and new fisheries guidelines are urgent for the equitable use of fisheries resources without compromising the goals of a protected area.